Dysembrioplastyczny guz nerwowo-nabłonkowy (DNT) u 9-letniego chłopca - od objawu do rozpoznania - Witkowska-Sędek, Ewelina; Krawczyk, Monika; Lipska, Elżbieta; Pyrżak, Beata (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Dysembryoplastic neuroepithelial tumour (DNT) is a rare benign tumour of central nervous system. It is diagnosed mainly in children and adolescents. The main symptoms are drug-resistant seizures, and a neurological examination does not normally indicate any symptoms of central nervous system damage. The tumour has typical appearance in the magnetic resonance imaging (MRI). Neurosurgical treatment is usually successful, although there are reported cases of failure after surgery or malignant transformation. This paper presents the case of a 9-year-old boy, referred to the hospital because of episodes of paroxysmal numbness and tremors of the right upper limb and right cheek initially interpreted as tetany. We describe the conducted differential diagnosis including disorders of calcium-phosphate metabolism, seizure disorders, ischaemic changes and organic changes in the central nervous system. The paper also discusses differentiation of tetany and partial seizures associated with the presence of a tumour in the central nervous system. The patient was diagnosed with epilepsy which, despite partial tumour removal, needs further pharmacological treatment. The management strategy for this case of drug-resistant epilepsy caused by DNT localised in the eloquent brain area is presented.